Gaucher disease: A diagnostic approach, clinical evolution and review - Silva, Bárbara Pereira; Souza, Mariana Araújo e; Castro , Catarina Sampaio de; Carvalho, Caroline Aquino de; Rodrigues, Bruno Piffer; Costa, Matheus Monteiro; Palheta, Jêmina Norâmy Neves; Barbosa, Bruno Cruvinel; Machado, Rafaela Araújo; Issy , Gabriela Zinhani; Borelli, Jamile Gonçalves; Munareto , Matheus Luís Braga; et al. (Seven Editora, 2023)
Introducion: Gaucher disease is an inherited metabolic disorder caused by a mutation in the GBA1 gene, resulting in deficiency of the enzyme beta-glucosidase and accumulation of glucocerebroside in tissues. This disease, which is an autosomal recessive inheritance, affects organs such as the spleen, liver, bone marrow and central nervous system. Case Presentation: A 23-year-old male was referred to the internal medicine service for evaluation of hepatosplenomegaly and anemia. She reports persistent lower extremity pain for a period of 5 years and increased abdominal volume. No history of comorbidities or regular use of medication. Discussion: There are three phenotypes of the disease with varied clinical manifestations: type I (non-neuropathic) is the most common, type II (acute neuropathic) is more severe, with acute neurological impairment and poor prognosis, and type III (chronic neuropathic) is less severe. The incidence is estimated at 1 in 60,000 in the general population. The main symptoms include hepatosplenomegaly, thrombocytopenia, anemia, and bone pain. Based on the premise that Gaucher Disease is difficult to diagnose early due to the similar clinical picture with different diseases, this work aims to delimit the signs and symptoms of the disease and its most affected age group to cover a greater recognition of this rare condition, facilitating the appropriate treatment of these patients. Conclusion: The analysis of the articles showed that the diagnosis is made through acid beta-glucosidase enzyme activity tests or detection of Gaucher cells in tissues and its treatment involves specific enzyme replacement, such as the use of alpha- taglycerase. DOI:https://doi.org/10.56238/sevened2023.006-006